Implikatur Percakapan pada Novel Oriana’s Wedding Diary Karya Ayana Kamila dan Implementasinya terhadap Pembelajaran Bahasa Indonesia - Errika Anandita; Diena San Fauziya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the types of conversational implicatures found in the novel Oriana's Wedding Diary by Ayana Kamila, as well as their implementation in Indonesian language learning in high school. The method used in this research is a qualitative descriptive method. The subject of this research is the novel Oriana's Wedding Diary by Ayana Kamila. Data collection techniques in this research used note-reading and literature study techniques. The results of this research were that several types of conversational implicatures were found in the novel, including: 1) General conversational implicatures, 6 data were found containing general conversational implications in the novel. 2) Specific conversational implicatures, 4 data were found containing general conversational implications in the novel. 3) Scale conversational implicatures, 3 data were found containing general conversational implications in the novel. The results of this conversational implicature research can also be implemented in high school in several materials, such as anecdote text material, fiction and non-fiction book material, and finally in historical story (novel) text material. In learning materials there are often sentences that can be interpreted in various ways. By understanding implicature, it is hoped that it can reduce confusion in interpreting the meaning that students have regarding these sentences.